(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The primary objective of this study is to identify the factors affecting the capital adequacy ratio (CAR) of institutions operating in securities activities in the Saudi Stock Exchange. To achieve this objective, the study adopted an analytical methodology, collecting data from various sources, such as statistical reports and bulletins issued by the Capital Market Authority (CMA) and annual statistical reports issued by the Saudi Stock Exchange (Tadawul). This data was analyzed using appropriate statistical and analytical tools. The study used a simple linear regression approach to determine the impact of each independent variable separately from the following: (credit risk, market risk, financial leverage measured by (total debt to total assets ratio), financial leverage measured by (total debt to total equity ratio), return on assets, and return on equity) on the CAR of institutions operating in securities activities in the Saudi Stock Exchange. It also used a multiple linear regression approach to determine the combined impact of all these variables on the CAR of institutions operating in securities activities in the Saudi Stock Exchange. The study reached several results, the most important of which are: the existence of a strong statistically significant direct correlation between the factors under study and the capital adequacy coverage rate of institutions operating in securities activity in the Saudi Stock Exchange. The results of simple linear regression and multiple linear regression also confirmed the existence of a positive statistically significant effect of all the factors under study on the capital adequacy coverage rate of institutions operating in securities activity in Saudi Stock Exchange. Based on these results, the study recommended the necessity of strengthening and enhancing the level of capital adequacy of institutions operating in securities activity in the Saudi Stock Exchange, and the necessity of supporting the efficiency and stability of the financial system of institutions operating in securities activity in the Saudi Stock Exchange.